Aggregate Production Planning of Marie Biscuit: A Case Study at a Biscuit Factory in Malang - Lestari, Endah Rahayu; Astuti, Retno; Mardiastutik, Heny (Fakultas Teknologi Pertanian Universitas Brawijaya, 2005)
The aim of this research were to forecast a weekly demand of marie biscuit in the next 6 months and to determine the optimal production aggregate planning that minimizes total cost. The planning, made for the period of August 2005 to January 2006, was based on the previous weekly demand in the period from August 2004 until July 2005. The demand of marie biscuit was forecasted using Wintersâ for Additive Method that produced the least mean square error and then the demand forecasting was obtained by means of the Minitab for Windows Version 14. A weekly inventory and an aggregate production were planned using the Dynamic Programming approach by means of a computer software which was developed using the Delphi for Windows version 5. The results showed that the highest demand was found in the forth week of January 2006 (2,534 kg ) and the lowest one (2,394 kg) was predicted to occur in the first week of August 2005. The weekly inventory level of the marie biscuit factory was between 185 kg to 225 kg in 24 weeks planning horizon. Overtime works would be necessary if the demand exceed the maximum regular production capacity. However, in case of the demand and the production quantity were lower than that of the regular production capacity, an introduction of undertime cost in the first and third weeks of the planning horizon would reduce the total cost by Rp 73,470 per week. The minimum total cost of the aggregate marie biscuit production planning in 24 weeks planning horizon was Rp 96,602,174. Â Key words: aggregate production planning, demand forecasting, Dynamic Programming